Placebo effects in psychiatry: mediators and moderators. (March 2015) - Weimer, Katja; Colloca, Luana; Enck, Paul
Summary A strong placebo response in psychiatric disorders has been noted for the past 50 years and various attempts have been made to identify predictors of it, by use of meta-analyses of randomised controlled trials and laboratory studies. We reviewed 31 meta-analyses and systematic reviews of more than 500 randomised placebo-controlled trials across psychiatry (depression, schizophrenia, mania, attention-deficit hyperactivity disorder, autism, psychosis, binge-eating disorder, and addiction) for factors identified to be associated with increased placebo response. Of 20 factors discussed, only three were often linked to high placebo responses: low baseline severity of symptoms, more recent trials, and unbalanced randomisation (more patients randomly assigned to drug than placebo). Randomised controlled trials in non-drug therapy have not added further predictors, and laboratory studies with psychological, brain, and genetic approaches have not been successful in identifying predictors of placebo responses. This comprehensive Review suggests that predictors of the placebo response are still to be discovered, the response probably has more than one mediator, and that different and distinct moderators are probably what cause the placebo response within psychiatry and beyond.